Effect of isothermal heat treatment on crystallinity, tensile strength and failure mode of CF/PPS laminate. (June 2021) - Liu, Yankuan; Zhou, Xuelin; Wang, Zhiping
The present work concentrates on the crystallinity, tensile strength and failure mode of CF/PPS laminate subjected to isothermal heat treatment of different temperatures and time periods. Results show that in the range of 100–210°C and 1–3 hours, with the increase of heat treatment temperature and time, both crystallinity and tensile strength of CF/PPS laminate increase firstly then decrease. Under the condition of 150°C-2 hours treatment, the CF/PPS has the optimal crystallinity level of 65.3% and the optimal tensile strength with a value of 718.2 MPa. Compared with the as-received specimen without heat treatment, the crystallinity and tensile strength have been increased by 46.4% and 15.3%, respectively. A laser confocal microscope has been used to observe and analyze the fracture morphologies of the specimens, results show that the failure modes of the specimens under conditions of 100°C and 150°C isothermal heat treatment are fiber extraction and fiber breakage, respectively, and both are AGM, while that of 210°C is debonding and delamination, which is DGM.